PENDALAMAN MATERI KAS/BANK DALAM PROGRAM ACCURATE BAGI SISWA/I SMK KRISTEN RAHMANI - Wijoyo, Amin; Cherry Tanichi; Nicholas Richardson3 (Jurnal Serina Abdimas, 2024)
Exploration of material on the use of accounting programs in inputting company transactions, especially cash and bank transactions for students at SMK Kristen Rahmani as part of Community Service (PKM) activities. This activity involves active participation from lecturers and students from Tarumanagara University with the aim of having a positive impact on the education ecosystem in Indonesia. This program contributes by providing additional knowledge about the use of accounting programs in inputting company transactions, especially cash and bank transactions. The delivery of material regarding program use and input was carried out directly at the Kristen Rahmani Vocational School on September 26 2024, and was attended by 15 students of the Rahmani Kristen Vocational School. The significance of this activity lies in its two main impacts, namely providing practical insight into the use of accounting programs in inputting company cash and bank transactions and expanding students' general understanding of accurate programs. Strengthening understanding of this material was tested through an oral quiz which was taken by all participants and the results showed that 80% of Rahmani Kristen Vocational School students managed to answer correctly, this reflects their deep understanding of the use of accounting programs in inputting company transactions, especially cash and bank transactions. These results provide evidence of the program's effectiveness in encouraging the achievement of substantial learning outcomes among participating students. ABSTRAK Pendalaman materi penggunaan program akuntansi dalam menginput transaksi perusahaan, khususnya transaksi kas dan bank bagi murid siswa/i di SMK Kristen Rahmani sebagai bagian dari kegiatan Pengabdian Kepada Masyarakat (PKM) sangat penting. Kegiatan ini melibatkan partisipasi aktif dari para dosen dan mahasiswa/i dari Universitas Tarumanagara dengan tujuan memberikan dampak positif pada ekosistem pendidikan di Indonesia. Program ini memberikan kontribusi besar dengan menyediakan pengetahuan tambahan tentang penggunaan program akuntansi dalam menginput transaksi perusahaan, khususnya transaksi kas dan bank. Penyampaian materi mengenai penggunaan program dan penginputan dilakukan secara langsung di SMK Kristen Rahmani pada tanggal 26 September 2024, dan dihadiri oleh 15 murid siswa/i SMK Kristen Rahmani. Signifikansi dari kegiatan ini terletak pada dua dampak utamanya, yaitu memberikan wawasan praktis tentang penggunaan program akuntansi dalam menginput transaksi kas dan bank perusahaan serta memperluas pemahaman umum siswa tentang program Accurate. Penguatan pemahaman terhadap materi ini diuji melalui kuis lisan yang diikuti oleh seluruh peserta dan hasilnya menunjukan sebanyak 80% siswa SMK Kristen Rahmani berhasil menjawab dengan benar. Hal tersebut mencerminkan pemahaman mendalam mereka mengenai penggunaan program akuntansi dalam menginput transaksi perusahaan, khususnya transaksi kas dan bank. Hasil ini menjadi bukti keefektifan program dalam mendorong pencapaian hasil belajar yang substansial di kalangan siswa yang berpartisipasi.